Knockout of Lysosomal Enzyme-Targeting Gene Causes Abnormalities in Mouse Pup Isolation Calls - Barnes, Terra D.; Holy, Timothy E. (Frontiers in Behavioral Neuroscience, 2017)
Humans lacking a working copy of the GNPTAB gene suffer from the metabolic disease Mucolipidosis type II (MLII). MLII symptoms include mental retardation, skeletal deformities and cartilage defects as well as a speech delay with most subjects unable to utter single words[1-3]. Here we asked whether mice lacking a copy of Gnptab gene exhibited vocal abnormities. We recorded ultrasonic vocalizations from 5 and 8 day old mice separated from their mother and littermates. Although Gnptab -/- pups emitted a similar number of calls, several features of the calls were different from their wild type littermates. Gnptab -/- mice showed a decrease in the length of calls, an increase in the intra-bout pause duration, significantly fewer pitch jumps with smaller mean size, and an increase in the number of isolated calls. In addition, Gnptab -/- mice vocalizations had less power, particularly in the higher frequencies. Gnptab +/- mouse vocalizations did not appear to be affected. We then attempted to classify these recordings using these features to determine the genotype of the animal. We were able to correctly identify 87% of the recordings as either Gnptab -/- or Gnptab +/+ pup, significantly better than chance, demonstrating that genotype is a strong predictor of vocalization phenotype. These data show that deletion of genes in the lysosomal enzyme targeting pathway affect mouse pup isolation calls.